Notes on the 'Eirde House,' at Culsh, in Tarland, Aberdeenshire (Proceedings of the Society of Antiquaries of Scotland, 1865)
The author describes the damage caused by visitors to the souterrain at Culsh in the decade since it was first excavated in 1854. He notes that the local farmer and tenant have attempted to mitigate the damage by adding a wooden support, a lockable door and by replacing some of the stone walls. A plan of the souterrain is also included. Meeting notes for 14 March, 1864 are appended.